2022
DOI: 10.1037/tra0000558
|View full text |Cite
|
Sign up to set email alerts
|

Preventing risk for posttraumatic stress following childbirth: Visual biofeedback during childbirth increases maternal connectedness to her newborn thereby preventing risk for posttraumatic stress following childbirth.

Abstract: Objective: Mounting evidence indicates the detrimental impact of posttraumatic stress following childbirth (PTS-FC). Nevertheless, research on preventive strategies is scarce. We recently reported that ultrasound visual biofeedback during second stage of labor was associated with immediate beneficial medical outcomes (increased pushing efficacy, decreased perineal tearing), as well as greater feelings of maternal connectedness toward her newborn immediately postlabor. The current study assessed the potential l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…However, although motherhood is assumed to be a joyous experience, for many women, pregnancy and childbirth are stressful, traumatic experiences (Ayers & Pickering, 2001; Caparros-Gonzalez, Perra, et al, 2019; Dekel et al, 2017). Studies have shown that traumatic childbirth can provoke severe psychological distress in mothers, some of whom may consequently develop postpartum posttraumatic stress disorder (PP-PTSD; Ayers et al, 2016; Schlesinger et al, 2020). According to recent reviews and meta-analyses, 3.1–6.3% of women suffer from this disorder after childbirth, a figure that rises to 15.7–18.9% among high-risk women, such as those with a history of psychiatric disorder and/or complications during childbirth (Dekel et al, 2017; Grekin & O’Hara, 2014; Yildiz et al, 2017).…”
mentioning
confidence: 99%
“…However, although motherhood is assumed to be a joyous experience, for many women, pregnancy and childbirth are stressful, traumatic experiences (Ayers & Pickering, 2001; Caparros-Gonzalez, Perra, et al, 2019; Dekel et al, 2017). Studies have shown that traumatic childbirth can provoke severe psychological distress in mothers, some of whom may consequently develop postpartum posttraumatic stress disorder (PP-PTSD; Ayers et al, 2016; Schlesinger et al, 2020). According to recent reviews and meta-analyses, 3.1–6.3% of women suffer from this disorder after childbirth, a figure that rises to 15.7–18.9% among high-risk women, such as those with a history of psychiatric disorder and/or complications during childbirth (Dekel et al, 2017; Grekin & O’Hara, 2014; Yildiz et al, 2017).…”
mentioning
confidence: 99%
“…Exclusion criteria were pre‐planned elective c‐section, premature birth, multiple pregnancy, and known serious medical issues at time of recruitment. A total of 192 participants was retained for the current study (39 were excluded because they received a biofeedback intervention during birth [Gilboa et al., 2018; Schlesinger et al., 2020]; 12 because of elective c‐section; and 15 because of overall missing data on the variables in this study). Data was collected at three time‐points: (T1) approximately 72 h after childbirth—during the post‐natal hospital stay; (T2) 1 month postpartum—during a home visit; (T3) 4 months postpartum—during a home visit.…”
Section: Methodsmentioning
confidence: 99%
“…Maternal feelings of bonding toward her infant/child refers to a mother's warm positive emotions and thoughts toward her child, and is known to be an important precursor of sensitive parenting (Le Bas et al., 2020). In general population samples, maternal PTS‐FC has often been found to associate with lower levels of maternal feelings of bonding toward her infant (e.g., Parfitt et al., 2014; Radoš et al., 2020; Schlesinger et al., 2020; Seng et al., 2013; Stuijfzand et al., 2020). Though some studies failed to find such links (Ayers et al., 2007; McDonald et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Participants were asked to view an ultrasound screen of fetal movement into the birth canal demonstrating their pushing efforts, providing a clear visual biofeedback. 12 This process led to a stronger maternal-neonatal connection, lower levels of acute stress during the hospital stay and lower levels of posttraumatic stress following childbirth at 1-month postpartum. The second study evaluated whether sonographic pushing during the second stage of labor improved birthing parameter compared with routine labor.…”
Section: Biofeedback Intervention On Labormentioning
confidence: 99%
“…Schlesinger and colleagues attempted to determine if an association was present between biofeedback, posttraumatic stress following childbirth, maternal connectedness or perineal tearing, and acute stress. Participants were asked to view an ultrasound screen of fetal movement into the birth canal demonstrating their pushing efforts, providing a clear visual biofeedback 12. This process led to a stronger maternal-neonatal connection, lower levels of acute stress during the hospital stay and lower levels of posttraumatic stress following childbirth at 1-month postpartum.…”
Section: Biofeedbackmentioning
confidence: 99%